A necklace sonar with adjustable scope range for assisting the visually impaired (2013)
A sonar based device with tactile feedback was developed to improve the mobility and independence of visually impaired individuals. It features a transceiver/receiver, a potentiometer, a microcontroller, a rechargeable polymer lithium ion battery, and a Nokia Cell phone vibrator. All components are commercially available and housed in a custom acrylic package with 86 mm × 34 mm × 12 mm in dimension, and 120 grms in weight. Additionally, the device features an adjustable detection scheme for user customization of distance range, and a tactile feedback system that avoids interference with auditory sensory information. The device was tested for its navigational efficacy in an artificial indoor environment, and in a live outdoor setting. Ten subjects (9 males and 1 female), with a mean age of 35 years-old (range: 17 to 52) were presented with a series of navigational tasks resulting in considerable reduction of head, shoulder, chest, and arms collisions during their locomotion. We conclude that this device greatly improves the mobility and safety of visually impaired individuals.